2015
DOI: 10.1103/physrevlett.115.175701
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Photon Correlation Spectroscopy Reveals Intermittent Aging Dynamics in a Metallic Glass

Abstract: We use coherent X-rays to probe the aging dynamics of a metallic glass directly on the atomic level. Contrary to the common assumption of a steady slowing down of the dynamics usually observed in macroscopic studies, we show that the structural relaxation processes underlying aging in this metallic glass are intermittent and highly heterogeneous at the atomic scale. Moreover, physical aging is triggered by cooperative atomic rearrangements, driven by the relaxation of internal stresses. The rich diversity of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
107
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(132 citation statements)
references
References 41 publications
17
107
3
Order By: Relevance
“…2(b)]. A similar stationary dynamics close to Tg was reported in recent XPCS studies on the Pd43Cu27Ni10P20 BMG 11 and also observed at low temperatures in hyper-quenched metallic glass ribbons subjected to long annealing times. 8,10 This crossover into a stationary dynamics regime and subsequent lack of aging in metallic glasses on the atomic length scale is a result of configurational changes to the glassy structure, which run independently of macroscopic density changes.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…2(b)]. A similar stationary dynamics close to Tg was reported in recent XPCS studies on the Pd43Cu27Ni10P20 BMG 11 and also observed at low temperatures in hyper-quenched metallic glass ribbons subjected to long annealing times. 8,10 This crossover into a stationary dynamics regime and subsequent lack of aging in metallic glasses on the atomic length scale is a result of configurational changes to the glassy structure, which run independently of macroscopic density changes.…”
Section: Resultssupporting
confidence: 60%
“…So far, we are unaware of any work that has thus far provided a direct link between Eshelby events and aging in metallic glasses, although recent studies have highlighted the important role played by atomic-level stresses. 11,13,32 The decrease in β near Tg reflects the system's close proximity to its equilibrium state (supercooled liquid), where the microscopic dynamics is indeed characterized by stretched exponential correlation functions, in accord with a heterogeneous dynamics scenario. [33][34][35] Upon cooling from the liquid, β increases smoothly and becomes constant, suggesting a continuous evolution from the supercooled liquid to the glassy state.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Also, the potential connection to the observation of sudden collapse in many gels after an initial lag time [43] needs exploration. Whether the mechanisms discussed in the context of such low density materials can be extended to understand similar fast relaxations reported for denser aging glasses [44][45][46] also requires more investigations.…”
mentioning
confidence: 99%
“…The nature of dynamics for our suspensions have been found to be stationary by measuring two time correlation functions (not shown here) at a given wave vector [43,44].…”
Section: Saxs and Xpcs Measurementsmentioning
confidence: 99%